The Role of the Midwife in Postpartum Family Planning Services : A Case Study on Three Different Health Facilities in South Central Java (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
Postpartum family planning coverage in Central Java is below the national standard, or it only reached 26.8%. Postpartum mothers are at risk of getting pregnant if they do not use contraception. Modern contraceptives prevent 3.2 million of 5.6 million under-five deaths and 109,000 of 155,000 (70%) maternal deaths. Continuity of Midwifery Care during the extended postpartum period encourages mothers to use modern contraception to manage the pregnancy gap. This study aimed to explore midwifery services for Family Planning Postpartum from the perspective of providers and clients in three health facilities: hospitals (RS), Public Health Centers, and Independent Midwifery Practice (PMB). The research was implemented through a qualitative descriptive, a case study approach design in 2021. informants were ten postpartum mothers, nine midwives, two heads of Puskesmas, head division of Family Planning, Women and Children Empowerment (KBPPA) conducted an in-depth interview. The interviews were digitally recorded, transcribed, and analyzed using the Miles and Huberman method. Providers and clients identified several benefits of Postpartum Family Planning (KBPP). Midwives stated several obstacles in providing services, such as limited counseling time during labor and lack of support from hospital management. The competence of midwives constrained KBPP services at the Puskesmas. There were still few midwives at the Puskesmas certified to provide Long Term Contraception Method services. Midwives were also overloaded with work during the pandemic. Obstacles in the Independent Midwifery Practice were the lack of IMP with clinical networks and the limited authority of the midwife. Meanwhile, postpartum mothers' barriers included lack of knowledge about fertility and KBPP, worry about side effects, and the husband's lack of support. Therefore, optimizing the referral mechanism for long-term contraception in advanced health facilities is necessary. Continuity of care midwives and integration of services will increase coverage of postpartum contraception.